Identification of coronary artery lesions and tactics of surgical treatment in patients with chronic lower limb ischemia - V. S. Arakelyan; R. N. Lysyy; A. S. Gagloeva (Атеротромбоз)
Introduction. Ischemic heart disease is undoubtedly the main factor that significantly aggravates the condition of patients with chronic lower limb ischemia in the perioperative period.Aim. To establish the expediency of mandatory performance of selective polypositional coronary angiography in patients with chronic ischemia of the lower extremities to determine the stages of surgical intervention and prevent cardiac complications.Materials and methods. The study included 285 patients, treated to the Department of arterial pathology surgery of the Bakulev National Medical Research Center of Cardiovascular Surgery with a diagnosis of chronic lower limb ischemia. The patients were divided into 2 groups. The main group included 139 patients admitted in 2016. The control group – 146 patients admitted in 1989. In the main group, all patients underwent coronary angiography. In the control group, coronary angiography was performed only in patients with a clinical picture of coronary artery disease or in asymptomatic patients after positive stress tests.Results and discussion. After analysis of coronary angiograms in patients of the main group, out of 139 patients included in the study, 124 (89.2%) had a lesion of at least 1 coronary artery >50%; and in 101 (72.7%) patients, at least 1 coronary artery was affected >70%. In the main group, cardiac complications were noted in 6 (4.32%) patients, while in the control group they were detected in 21 (14.4%) cases. These complications appeared due to the underestimation of the state of the coronary bed, based only on the results of stress tests.Conclusions. Selective polypositional coronary angiography is the main method for detecting asymptomatic significant coronary artery disease in patients with CLCI, which improves the immediate results of surgical treatment by reducing the incidence of cardiac complications.